Intended and Unintended Pregnancies Worldwide in 2012 and Recent Trends. Issue 3 (September 2014) - Sedgh, Gilda; Singh, Susheela; Hussain, Rubina
<x xml:space="preserve">Abstract</x> Periodic estimation of the incidence of global unintended pregnancy can help demonstrate the need for and impact of family planning programs. We draw upon multiple sources of data to estimate pregnancy incidence by intention status and outcome at worldwide, regional, and subregional levels in 2012 and to assess recent trends using previously published estimates for 2008 and 1995. We find that 213 million pregnancies occurred in 2012, up slightly from 211 million in 2008. The global pregnancy rate decreased only slightly from 2008 to 2012, after declining substantially between 1995 and 2008. Eighty‐five million pregnancies, representing 40 percent of all pregnancies, were unintended in 2012. Of these, 50 percent ended in abortion, 13 percent ended in miscarriage, and 38 percent resulted in an unplanned birth. The unintended pregnancy rate continued to decline in Africa and in the Latin America and Caribbean region. If the aims of the London Summit on Family Planning are carried out, the incidence of unwanted and mistimed pregnancies should decline in the coming years.